Program Intrakurikuler Berbasis Multiple Intelligences Pada Sekolah Dasar Islam - Muslimin (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
Fundamental problems are also very complex at the child's education or primary school level. Most of the implementation is oriented to hone memorization skills in order to develop thinking skills. Children are not oriented to the ability to understand the material to solve the problems they face. In this context, the application of multiple intelligences-based learning is needed SDI AL Azhar Kota Kediri. In order to obtain data, this study used a qualitative approach. As a result, the implementation of intracurricular learning based on the development of multiple intelligences is carried out in three stages, namely a) Implementation of Multiple Intelligences Research (MIR); b) Lesson Plans; c) Talent and Interest Mapping. While the models developed are daily activities, weekly activities, moonly activities and 4 learning models which are then also applied in various extracurricular activities. So that through these activities can help develop 9 intelligences in students. As a result, daily activities and learning models can have an impact on the intelligence of students, as well as participating in extracurricular activities so that they can develop the potential in students.